Epididymal alveolar echinococcosis and tuberculosis co-infection: A case report - Chuanchuan Liu; Hainin Fan (IDCases, 2024)
Alveolar echinococcosis (AE) is a common and significant public health problem caused by the larvae of the Echinococcus multilocularis. The occurrence of epididymal AE is rare and often overlooked in combination with mycobacterium tuberculosis infection. We report a case of a 34-year-old man who presented with right-sided scrotal enlargement with pain. Physical examination revealed an enlarged right scrotum with rupture. CT examination showed a blurred border and non-enhancing lesion on the right epididymis. Postoperative pathology and molecular biology identified an epididymal E. multilocularis infection. We report this rare case to emphasise the difficulty of preoperative diagnosis and the importance of complete surgical excision of the lesion.